Effect of phosphorylated long‐chain inulin on the dough rheology and steamed bread quality. (2nd December 2022) - Zhao, Yingyu; Luo, Denglin; Yue, Chonghui; Wang, Libo; Xiang, Jinle; Guo, Jinying; Li, Peiyan; Huang, Jihong; Zhang, Kangyi
Summary: Long‐chain inulin is found to damage the quality of flour products even at low addition amounts due to its molecular structure. The purpose of this study is to investigate the effect of modified long‐chain inulin on the properties of the dough and steamed bread. The rheological properties of dough, as well as the structure, moisture distribution and retrogradation enthalpy of the steamed bread, were evaluated with a rheometer, a texture analyser, low‐field nuclear magnetic resonance and a spectrometer differential scanning calorimetry, respectively. The results showed that the phosphorylation of long‐chain inulin (PFXL) addition in wheat flour could decrease the G′ and G′′ of the dough, which exerted different effects depending on the substitution level. The addition of PFXL (≤5.0%) contributed to a uniform crumb with well‐distributed cells of steamed bread. During the storage of steamed bread, PFXL slowed down the retrogradation process, especially at 5% of substitution level. In conclusion, the phosphorylation of long‐chain inulin is an effective method to broaden its potential applications such as improving the nutritional and textural quality of steamed bread. Abstract : The addition of phosphorylated long‐chain inulin in wheat flour improves the quality of steamed bread, especially in terms of its anti‐staling aspect.